Effectiveness of Interactive Learning Media (ILM) on English Vocabulary Mastery of Indonesian Students: A Meta-Analysis Study - Umi Muabidah; Anton Agus Setiawan (Jurnal Pendidikan Progresif, 2024)
Effectiveness of interactive learning media (ILM) on english vocabulary mastery of Indonesian Students: A meta-analysis study. Previous research examining the effectiveness of interactive learning media (ILM) shows inconsistent results. Objectives: This research aims to conduct a meta-analysis study regarding the effectiveness of using ILM on English vocabulary mastery and identify what factors moderate the influence of ILM on students' English vocabulary mastery. Methods: This reserch uses meta-analysis method. This meta-analysis synthesized 20 primary studies that met the inclusion criteria. Findings: The results of analysis using the random-effects approach obtained a combined effect value of 1.10 (large effect). This value shows that the use of ILM has a big influence and is more effective than conventional learning media. The results of the moderator variable analysis show that the variables sample size, education level, region, and type of ILM moderate the impact of ILM use on students' English vocabulary mastery. Conclusion: The findings of this meta-analysis provide more accurate results regarding variation effects of inconsistent size and enrich knowledge about the effectiveness of using ILM. Keywords: interactive learning media, meta-analysis, and mastery vocabulary.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202483